Should the Red Dragon arise? Assessing China's options vis-à-vis the enactment of a domestic space resources utilization law. (May 2017) - Hao, Liu; Tronchetti, Fabio
Abstract: The past couple of years have witnesses one of the most exciting, yet controversial, developments in the field of space law, namely the adoption of domestic laws authorizing the (private) appropriation and utilization of outer space resources. Even though the technology to effectively mine resources in outer space is still under development countries like the United States and Luxembourg have taken this legislative step as a mean to promote the growth of a domestic private space mining sector. The enactment of national space resources utilization laws has generated extensive interest both within academic circles and official fora, such as the United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS). In this context, several countries have expressed their opinion about these initiatives, by often criticizing their legality vis-à-vis international space law. Despite this remarkable level of interest there is a country that throughout this process has maintained a low profile, namely China. Indeed, China has neither reacted to the US and Luxembourgish moves nor has officially commented on the lawfulness of domestic space mining laws. This conduct is particularly relevant not only in the light of the growing importance of the Chinese space program but also if one considers that China is the country most involved in the exploration and study of celestial bodies and their resources, particularly the Moon. For this reasons it would have been legitimate to expect China to have a more engaged behavior. However, China has acted otherwise. It seems thus worth evaluating whether China should maintain this 'wait and see' approach or should instead switch towards a more assertive position, both internationally and domestically, especially one which includes the adoption of a space resources utilization act.